Knowledge, attitudes, and practices of students towards total quality management in education at High Institute of Health Sciences in Sana'a, Yemen - Mohaideen, Aref Yousuf Mosa'ad; Azimatun Noor Aizuddin, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction The quality of education is one of the controversial topics and vital issues that requires more emphases from researchers due to the current challenges in education at the university level. Involvement and participation from the studentis essential to implement quality assurance and to reach for academic accreditation. The aim of this study is to assess knowledge, attitudes, and practices (KAP) of students towards TQM in education and its influencing factorsatHigh Institute of Health Sciences (HIHS) in Sana'a, Yemen. Methods A cross-sectional study using a self-administered questionnaire was conducted in 2016. A total of 208 students from second and third study levels in HIHS had participated from 268 students were observed (study population). Descriptive statistics, chi-square, and one-way ANOVA were used to determine the association between students’ KAP towards TQM in education with its influencing factors. Results Mean age of the students were 22.44(SD±2.027) year old. Majority of HIHS students were male 135 (64.9%) and 108 (51.9%) were from the third studying level. The highest students' KAP scores were 53.4%, 65.4%, and 41.3% for good knowledge, good attitudes, and moderate practices respectively. Education Department was found to be significantly associated with students' knowledge and practices with p<0.05. In addition, the means of knowledge, attitudes, and practices were higher among pharmacy, radiology, and physiotherapy students respectively than laboratory students. Students' practices were found to be significantly associated with management, academic, and material factors with p<0.001. Conclusions HIHS students were observed to have good knowledge, good attitudes, and moderate practices towards TQM.